Information Response Models: An Integrated Approach - Smith, Robert E.; Swinyard, William R. (Journal of Marketing, 1982)
This article reviews the development of advertising response theories including the hierarchy of effects and low involvement learning models. By combining concepts from several areas, a new “integrated information response model” is proposed that appears to be in close accord with existing evidence.